Effects of grazing intensity and topography on steppe vegetation and soil properties of Mt. Aragats, Armenia - Marine NAVASARDYAN; Tatevik SARGSYAN; Harutyun DAVEYAN; Eleni M. ABRAHAM (Notulae Botanicae Horti Agrobotanici Cluj-Napoca, 2025)
Steppes are large ecosystems and diverse in plant composition and soils-climatic conditions. Steppes have been used for pastoralism for centuries. Few studies have considered interactive effects of grazing intensity and topography on steppe productivity, plant composition and soil properties. The study was conducted at no grazed, moderately and freely grazed sites of two steppe areas located at 1500-1800 m a.s.l. of south-east slope of Mt. Aragats. Slope exposition, slope inclination, mean temperature and precipitation for steppe areas were also assessed. Aboveground biomass and plant and soil chemical analysis were done by the national standard methods, and influencing factors were extracted by RDA. Results showed that the steppe aboveground biomass decreased significantly with the grazing intensity increasing (55-70%), no matter of soil type as was shown by RDA analysis. Vegetation height responds to grazing intensity independently of topography and environmental factors. Nitrogen content in plants was mainly affected by grazing and increased in freely grazed sites, while it had no effect on phosphorus and potassium content. Grazing intensity and topography and environmental factors did not affect soil physicochemical properties. Only litter content was higher at moderately grazed sites on chernozem like soils. Comparative analysis of the two steppe areas highlighted notable shifts in productivity and key soil properties, primarily driven by grazing pressure rather than environmental conditions. Therefore, effective conservation strategies and controlled grazing management are essential for sustainable land use and mitigating degradation in these ecosystems.